Pelaksanaan Pelvic Rocking dengan Birth Ball terhadap Kemajuan Persalinan - Rahmadyanti, Rahmadyanti; Hernawati, Lulu (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The aim of this study was to determine the effect of implementing pelvic rocking with a birth ball on the progress of labor. The method used was pre-experimental using a static group comparison design with accidental sampling technique. Two groups were selected from the sample, the intervention group performed pelvic rocking movements while monitoring the progress of labor in the control group. The research was conducted in November and December 2023. The sample consisted of 60 respondents. Independent Sample Test was used in data analysis. Research findings show that pelvic rocking with a birth ball has an impact on the course of labor, with a p-value of 0.000 < 0.05 and a confidence level of 95%. In short, pelvic rocking with a Birth ball makes it easier to rotate the baby into an optimal position so that the mother in labor can shorten the first stage, providing a feeling of comfort and relaxation, thereby helping the mother psychologically in processing pain. Keywords: Birth ball, Labor progress, Pelvic rocking